Small and Intermediate Calcium Activated Potassium Channels in the Heart: Role and Strategies in the Treatment of Cardiovascular Diseases - Weisbrod, David (Frontiers in Physiology, 2020)
Calcium-activated potassium channels are a heterogeneous family of channels, which, despite their different biophysical characteristics, structures and pharmacological signatures, play a role of transducer between the ubiquitous intracellular calcium signaling and the electric variations of the membrane. Although this family of channels was extensively described in various excitable and non-excitable tissues, an increase amount of evidences shows their functional role in the heart. This review aims to focus on the physiological role of the Small and Intermediate Calcium-activated Potassium channels, their contribution to cardiac pathologies and discuss further potential therapeutic strategies.